Abundant cytomegalovirus (CMV) reactive clonotypes in the CD8+ T cell receptor alpha repertoire following allogeneic transplantation. (8th March 2016) - Link, C. S.; Eugster, A.; Heidenreich, F.; Rücker‐Braun, E.; Schmiedgen, M.; Oelschlägel, U.; Kühn, D.; Dietz, S.; Fuchs, Y.; Dahl, A.; Domingues, A. M. J.; Klesse, C.; et al.
Summary: Allogeneic stem cell transplantation is potentially curative, but associated with post‐transplantation complications, including cytomegalovirus (CMV) infections. An effective immune response requires T cells recognizing CMV epitopes via their T cell receptors (TCRs). Little is known about the TCR repertoire, in particular the TCR‐α repertoire and its clinical relevance in patients following stem cell transplantation. Using next‐generation sequencing we examined the TCR‐α repertoire of CD8 + T cells and CMV‐specific CD8 + T cells in four patients. Additionally, we performed single‐cell TCR‐αβ sequencing of CMV‐specific CD8 + T cells. The TCR‐α composition of human leucocyte antigen (HLA)‐A*0201 CMVpp65– and CMVIE ‐specific T cells was oligoclonal and defined by few dominant clonotypes. Frequencies of single clonotypes reached up to 11% of all CD8 + T cells and half of the total CD8 + T cell repertoire was dominated by few CMV‐reactive clonotypes. Some TCR‐α clonotypes were shared between patients. Gene expression of the circulating CMV‐specific CD8 + T cells was consistent with chronically activated effector memory T cells. The CD8 + T cell response to CMV reactivation resulted in an expansion of a few TCR‐α clonotypes to dominate the CD8 + repertoires. These results warrant further larger studies to define the ability of oligoclonally expanded T cell clones to achieve an effective anti‐viral T cell response in this setting.